1998
DOI: 10.1021/tx970169z
|View full text |Cite
|
Sign up to set email alerts
|

Stable Acetaldehyde−Protein Adducts as Biomarkers of Alcohol Exposure

Abstract: The consumption of alcoholic beverages has been associated with increased risks of a number of chronic disorders including cancers. It is still not clear whether ethyl alcohol or other components such as metabolites are directly involved in the carcinogenic process or whether the effects are due to the modulation of metabolism of other carcinogens. At present, there is no good biomarker of alcohol intake, particularly at low or moderate levels of consumption. A number of studies have shown the ability of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…There appears to be a fine balance between internal cyclization of aldehyde‐derived protein adducts,13, 14 intramolecular reactions with adjacent nucleophiles as observed in histone H4,38–40, and intermolecular cross‐linking reactions that are observed with HNE 41, 42. In studies with model peptides derived from hemoglobin, Conduah Birt et al 43 demonstrated that with monofunctional aldehydic electrophiles such as acetaldehyde, the major products arose from Schiff base formation at the N‐terminal valine residue. However, the α,β ‐unsaturated aldehyde that is present in 4‐ONE significantly alters regioselectivity of the reaction with nucleophilic amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a fine balance between internal cyclization of aldehyde‐derived protein adducts,13, 14 intramolecular reactions with adjacent nucleophiles as observed in histone H4,38–40, and intermolecular cross‐linking reactions that are observed with HNE 41, 42. In studies with model peptides derived from hemoglobin, Conduah Birt et al 43 demonstrated that with monofunctional aldehydic electrophiles such as acetaldehyde, the major products arose from Schiff base formation at the N‐terminal valine residue. However, the α,β ‐unsaturated aldehyde that is present in 4‐ONE significantly alters regioselectivity of the reaction with nucleophilic amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…Since those first attempts, a number of studies have been conducted on the subject of protein haptenation in an effort to detect, characterize and quantify the process. Although not always related to skin sensitization, these studies have nevertheless achieved important milestones in our understanding of protein haptenation mechanisms (22–29). Over recent years, methodology applied to characterize protein–hapten binding has improved substantially, including immunochemistry, nuclear magnetic resonance (NMR) and mass spectrometry.…”
Section: Chemistrymentioning
confidence: 99%
“…Peptides with sequences analogous to a part of human proteins are also used to assess chemical reactivity. DS3 peptide, which has a sequence analogous to the N‐terminal part of the human globin (sequence VLSPADKTNWGHEYRMFCQIG), was used to investigate binding of 4‐chlorobenzenediazonium hexafluorophosphate (27), acetaldehyde (24) and 5‐chloro‐2‐methylisothiazol‐3‐one (44). Glycine apart, this peptide contains 1 residue of each of the commonly occurring amino acids.…”
Section: Chemistrymentioning
confidence: 99%
“…Acetaldehyde is a highly reactive metabolite implicated in causing cytotoxicity by binding tissue macromolecules and disrupting cellular functions (Lieber, 1997) through selective modification of amino acid residues resulting in the formation of stable adducts. At the molecular level, AcH reversibly binds to amino acid residues and N‐terminus of proteins, including hemoglobin and albumin (Brandsch et al., 2004; Conduah Birt et al., 1998; Hecht et al., 2001; Niemela et al., 1991; Wickramasinghe et al., 1994; Zhang et al., 2002). Furthermore, AcH adducts have been shown to increase paracellular permeability in vitro (Rao, 1998) by reversibly disrupting epithelial tight junctions (Atkinson and Rao, 2001), altering cellular differentiation and adhesion (Koivisto and Salaspuro, 1998), and attaching to plasma thrombin protein binding sites, thereby inactivating coagulation factors (Brecher and Adamu, 2002).…”
mentioning
confidence: 99%